Polish American Studies (JSTOR)
Polish American Studies is a peer-reviewed scholarly journal that welcomes articles, edited documents, bibliographies, reviews and other materials dealing with all aspects of the history and culture of Poles in the Western Hemisphere. It is a member of the History Cooperative and JSTOR electronic databases and is abstracted in Historical Abstracts, America: History and Life, and The Catholic Periodical and Literature Index.
Keywords: American Studies